Preparative Mass Spectrometry Using a Rotating‐Wall Mass Analyzer. Issue 20 (19th March 2020) - Su, Pei; Hu, Hang; Unsihuay, Daisy; Zhang, Di; Dainese, Tiziano; Diaz, Rosa E.; Lee, Jongsu; Gunaratne, Don K.; Wang, Haiyan; Maran, Flavio; Mei, Jianguo; Laskin, Julia
Abstract: The design of functional interfaces is central to both fundamental and applied research in materials science and energy technology. We introduce a new, broadly applicable technique for the precisely controlled high‐throughput preparation of well‐defined interfaces containing polyatomic species ranging from small ions to nanocrystals and large protein complexes. The mass‐dispersive deposition of ions onto surfaces is achieved using a rotating‐wall mass analyzer, a compact device which enables the separation of ions using low voltages and has a theoretically unlimited mass range. We demonstrate an efficient deposition of singly charged Au144 (SC4 H9 )60 ions (33.7 kDa), which opens up exciting opportunities for the structural characterization of nanocrystals and their assemblies using transmission electron microscopy. Our approach also enables the high‐throughput deposition of mass‐selected ions from multicomponent mixtures, which is of interest to the controlled preparation of surface gradients and rapid screening of molecules in mixtures for a specific property. Abstract : You spin me round : Preparative mass spectrometry using a rotating‐wall mass analyzer enables the deposition of well‐defined polyatomic ions from small molecules to nanoclusters and protein complexes as well as the high‐throughput separation and deposition of molecules from multicomponent mixtures. The approach is of interest to the design and preparation of functional interfaces and uses an inexpensive and compact instrumentation.